Determination of refractive index using surface plasmon resonance (SPR) and rigorous coupled wave analysis (RCWA) with a D-shaped optical fiber and a nano-gold grating. Issue 4 (3rd July 2020) - Ying, Yu; Wang, Jiakai; Hu, Nan; Xu, Ke; Sun, Liangliang; Si, Guangyuan
Abstract: A D-shaped optical-fiber refractive index sensor based on surface plasmon resonance is reported. Rigorous coupled-wave analysis was used to simulate the numerical modeling. The influences of different metal grating parameters on the coupling efficiency were studied and an optimal phase match was obtained. The results show that wavelength sensitivity of the proposed optical fiber sensor is as high as 0.925 μm/RIU for refractive index values from 1.35 to 1.43 with a high linearity value of 0.997. The reported structure may promote the development of high-performance biochemical sensing devices.